Implementasi Kepemimpinan Transformatif Kepala Madrasah Aliyah Ma’arif Cilageni Kadungora - Ari Prayoga; Rismaya Muharomah; Sutarti Sutarti (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2019)
Globalization requires humans to follow the path of life more broadly and openly, no exception in the world of education. In this era of change leadership is very important in guiding the improvement of madrasah achievement and development. The headmaster is a leader in the education unit. The success of madrasah headship leadership rests on one theory or leadership model. The purpose of this study was to determine the implementation of transformational leadership of madrasa in making changes in Madrasah Aliyah Ma’arif. This research uses a qualitative approach with descriptive methods. Data collection is done by interview, observation, and study documentation. Data analysis with extension of participation, perseverance of observation, analysis of negative skills, adequacy of references, detailed description and auditing. The results of this study indicate that; first, the transformative leadership style of the madrasa head is seen from the way he exerts an ideal influence on the madrasah community; second, motivating madrasa citizens and in making policies, so that it encourages changes in the culture of the organization and changes in the quality of madrasa.